Comparison of the Long-term Impact and Clinical Outcomes of Fewer Doses and Standard Doses of Human Papillomavirus Vaccine in the United States: A Database Study. Issue 9 (September 2020) - Rodriguez, Ana M.; Zeybek, Burak; Vaughn, Micah; Westra, Jordan; Kaul, Sapna; Montealegre, Jane R.; Lin, Yu-Li; Kuo, Yong-Fang
Abstract : (Abstracted from Cancer 2020;126:1656–1667) Human papillomavirus (HPV) is the most common sexually transmitted disease in the United States, and persistent infection with 1 of the 12 high-risk genotypes has been causally linked with development of cervical cancer. Several vaccines targeting high-risk genotypes have been developed and implemented.